Environmental and Psychological Factors as Predictors of Chronic Low Back Pain among Thai Elderly in Samutprakarn Province, Thailand - Arunsawas, Phakamat; Boonshuyar, Chaweewon; Aimyong, Natnaree (Journal of Health Research, 2017)
Background: Thailand has become to an aging society. In 2040, Thai elderly will be raise to more than the one-third of total population. Chronic low back pain (CLBP) is the most common symptom of musculoskeletal chronic pain in worldwide and very common in aging population. This study aimed to estimate the prevalence of CLBP and identify factors related to CLBP among the elderly. Methods: A cross-sectional study was conducted to determine elderly characteristics, environmental factors, and psychological factor in relation to CLBP. Face to face interviews and the observation of the sitting, standing, walking postures was conducted among 188 participants of elderly clubs in Phrapradaeng district, Samutprakarn province, Thailand. Results: The results showed that the prevalence of CLBP was 66.1 %. Only 22.7% was at mild intensity; followed by 23.8% and 19.6% at moderate and severe level respectively. Half (51.1%) of them was 60 to 69 years. About three-fifth was female (60.6%). Nutritional status as considered from their body mass index (BMI), 41.5% was obese while 21.3% was overweight. Majority of elderly (83.5%) have had chronic diseases. The most common three diseases were hypertension, dyslipidemia, and diabetes mellitus respectively. About 79.8% did exercise within the last three months. The majority had a correct posture on sitting and standing. Fifty-eight percent had a correct posture on walking. Number of chronic diseases, getting up from bed posture, and walking posture were significantly associated with CLBP. Conclusion: To reduce CLBP, improving postures in the daily activities and gait pattern among the elderly people for CLBP prevention is suggested.